2019
DOI: 10.1080/01694243.2019.1587224
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical noise (EN) technique: review of recent practical applications to corrosion electrochemistry research

Abstract: The ability to analyze different electrochemical corrosion phenomena, in-situ, without requiring any form of electrode perturbation has strongly attracted the attention of corrosion researchers towards the application of electrochemical noise (EN) analysis method. With the ability to analyze stochastic and chaotic electrode potential and current fluctuations at E OCP , the EN analysis method is capable of providing information about the kinetics and mechanism of metallic corrosion with accuracy that can match … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 138 publications
0
23
0
Order By: Relevance
“…The samples' electrochemical characterization and corrosion behaviour were studied using the potentiodynamic polarization as a function of time, in a chloride solution with two concentrations of 0.9 and 3.5 wt. % of NaCl at 25 o C, which is similar to the human body environment [18][19][20][21]. The electrochemical tests were performed using a model Bio-Logic SP-150 potentiostat measuring instrument.…”
Section: Fig 2 Schematic Of In-situ Coating Process By Hot Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples' electrochemical characterization and corrosion behaviour were studied using the potentiodynamic polarization as a function of time, in a chloride solution with two concentrations of 0.9 and 3.5 wt. % of NaCl at 25 o C, which is similar to the human body environment [18][19][20][21]. The electrochemical tests were performed using a model Bio-Logic SP-150 potentiostat measuring instrument.…”
Section: Fig 2 Schematic Of In-situ Coating Process By Hot Pressmentioning
confidence: 99%
“…The results showed that coating of 316L on Ti alloy reduced the wear rate of the powder alloy. In terms of the biocompatibility tests of coating austenitic stainless-steel alloy on Ti alloys, recent investigations [18,19] show that there is a relationship between pitting corrosion resistance and microbiologically induced corrosion (MIC), based on the similarities of the localized corrosion of MIC in nature, which is the phenomena of pitting and crevice corrosion. The previous paper of the author [17] indicates that the coated Ti6Al4V with 316L powder alloy, were tested in a bacterial environment of E. coli and S. aureus bacteria, and the results showed good antibacterial properties, no bacteria observed on the surface of 316L.…”
Section: Introductionmentioning
confidence: 99%
“…EN is a sensitive and nondestructive technique employed to simultaneously measure potential and current fluctuations as noise produced by the anodic and cathodic reactions. 32,33,[61][62][63][64] For polymer-coated metals, the current noise indicates changes in coating integrity, while the potential noise indicates passivity and the presence of electrolyte at the coating-metal interface. 22,65 A typical experimental setup is shown in Fig.…”
Section: Electrochemical Noisementioning
confidence: 99%
“…25,26 Techniques that measure impedance and the correlation between current, potential and time have been widely used to obtain mechanistic information on corrosion. 15,17,[27][28][29][30][31][32][33][34][35][36][37][38] Hence, this mini-review briefly explores the most commonly used electrochemical techniques in the evaluation of corrosion protection performance of polymeric coatings: open circuit potential (OCP), electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, electrochemical noise and scanning electrochemical microscopy (SECM). The mode of operation, acquisition of data, relevant equations and electrochemical variables, as well as the advantages and shortcomings of each technique, are also highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Although this hope has not been fully implemented but there has been some progress and the technique has been in use for corrosion monitoring. EN analysis is a reliable technique that allows metal corrosion determination without any kind of external potential perturbation [ 63 ]. EN is more suited to detect and quantify localized corrosion [ 60 ].…”
Section: Electrochemical Corrosion Monitoring Of Various Substratementioning
confidence: 99%